THE EFFECT OF THE IMPLEMENTATION OF COOPERATIVE TGT (TEAMS GAME TOURNAMENT) LEARNING MODEL-BASED ELEARNING APPLICATION UPON CLASS VII STUDENTS’ OUTCOMES OF SMP NEGERI 2 SINGARAJA - Febry Erawati, Ni Luh Putu (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2012)
The purposes of this study were to (1) determine the effect the implementation of cooperative TGT (Teams Game Tournament) learning modelbased e-learning application upon class VII students’ outcomes on ICT learning of SMP Negeri 2 Singaraja, and (2) study the response of the students to the implementation of cooperative TGT (Teams Game Tournament) learning modelbased e-learning application upon class VII students’ outcomes on ICT learning of SMP Negeri 2 Singaraja. This study belonged to a quasi-experimental research which was used a posttest-Only Control Group Design. The population of this study was class VII students of SMP Negeri 2 Singaraja in second semester in the academic year of 2011/2012 with the sample of the study were class VII E students as experimental group and class VII A students as control group. There were two kinds of variables in this study, they were (1) the independent variable was the media cooperative TGT (Teams Game Tournament) learning model-based e-learning application, and (2) the dependent variable was the students’ learning outcomes. The data were collected by using multiple-choice tests to measure cognitive domains and skill-test to measure the psychomotor domain. Then, the data of test results were analyzed by conducting the prerequisites that included normality and homogeneity tests. Then the data were analyzed by using t-test. Meanwhile, for the students’ response were analyzed by using the questionnaire method. Based on the results of normality and homogeneity tests on the results of both of the groups, it was found that the data of both samples were normal and homogeneous. For hypothesis testing was tested by using t-test, from the results of calculations obtained tcount = 14.234, meanwhile the ttable = 1.9925, therefore tcount> ttable then Ho was rejected and Ha was accepted. Furthermore, as many as 18.42% students responded very positively, 71.05% of students responded positively, 10.53% of students responded quite positively. It could be concluded that there was a significant differences on the implementation of cooperative TGT learning model-based e-learning application upon class VII students’ outcomes on ICT learning of SMP Negeri 2 Singaraja.